DIAGNOSIS OF MUCINOUS BREAST CANCER - E. К. Saribekyan; Е. А. Rasskazova; Е. N. Slavnova; L. А. Mitina (Сибирский онкологический журнал, 2016)
The paper presents the diagnostic results of 27 patients with mucinous breast cancer, which is a rare type of invasive ductal breast cancer accounting for less than 2% of all breast cancers. The role of radiological, histological and cytological examination in the diagnosis of mucinous breast cancer is evaluated. In cases with large tumors, it was difficult to differentiate mucinous breast cancer from fibrocystic and other benign breast lesions.